2016
DOI: 10.3141/2601-09
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Location–Movement Classification Method for Pedestrian and Bicycle Crash Typing

Abstract: Annual pedestrian and bicycle fatalities remained steady while motor vehicle fatalities declined in the United States during the past decade; this balance underscores the need for better methods of pedestrian and bicycle safety analysis. This study presents a new method for classifying pedestrian and bicycle crashes called the location–movement classification method (LMCM) and shows that the LMCM provides useful information that is not captured by a well-established NHTSA crash typology. Both typologies were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Like many agencies, the City of Milwaukee and Wisconsin Department of Transportation base nearly all of their transportation safety analyses on police-reported crash data ( 6 , 20 ). These data can be mapped easily to highlight roadway intersections and corridors that are crash hot spots.…”
Section: Discussionmentioning
confidence: 99%
“…Like many agencies, the City of Milwaukee and Wisconsin Department of Transportation base nearly all of their transportation safety analyses on police-reported crash data ( 6 , 20 ). These data can be mapped easily to highlight roadway intersections and corridors that are crash hot spots.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also revealed that while longer reports result in less missing information when compared to the standardized crash form, the average report still has a lot of missing information. Schneider and Stefanich ( 9 ) introduced the location-movement classification method (LMCM) to classify pedestrian and bicycle crashes, and demonstrated that the LMCM provides useful information that PBCAT does not capture. Both typologies were applied to 296 pedestrian and 229 bicycle crashes in Wisconsin reported between 2011 and 2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PBCAT is a computer program designed to assist in coding pedestrian and bicycle crashes, developed in the late 1990s and refined in 2006 (8,14). States including NC and Wisconsin have used it (15,16), but no national report of crash types using the PBCAT method exists, and no bicycle-specific crash typing has been published across multiple states in the past two decades. This is a result in part of the difficulty of comparing records that may lack critical information used to identify crash types without combing through crash reports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other typologies have been developed that may provide alternatives to PBCAT such as the Location Movement Classification Method developed in Wisconsin ( 16 ). However, this study focuses on PBCAT crash types since comparable data were available from multiple jurisdictions.…”
Section: Literature Reviewmentioning
confidence: 99%